Indocyanine Green and Arginine-Glycine-Aspartic Acid Complex Used in Intraoperative Visualization during Resection of Bladder Tumour - Li Peng; I. R. Kabirov; A. R. Kasinskaya; Jiaqi Wang; Wanhai Xu; E. K. Zhuk; R. A. Nuralieva (Креативная хирургия и онкология, 2019)
Introduction. Bladder cancer is one of the most common malignancies in humans, causing significant economic and social damage. In the connection, it is proposed to use a highly sensitive bladder cancer detection method, which also detects residual tumours. Additionally, the method can be used to determine the boundaries of the bladder tumour, namely through intraoperative fluorescence molecular imaging. The target agent was synthesised earlier with indocyanine green-arginine-glycine-aspartic acid, which is an integrin avß3-targeted in in vitro and in vivo bladder cancer models.Materials and methods. The toxicity of indocyanine green-arginine-glycine-aspartic acid (Agac-IG) was measured using the MTT-test. Urothelial carcinoma cell lines were introduced in Female BALB/nu and MB49 mice by means of tumour xenografts via injection in the back of the elbow area. Tumour growth was observed on a daily basis and tested by magnetic resonance imaging until it became suitable for in vivo experiments. Then, all the laboratory animals were divided into 2 groups: ig and AGAk-ig (150 μl, 0.2 mg/ml for all mice). Following this, the tumour was surgically removed. The removed tissue was subjected to a fluorescent microscopy on the basis of infrared-spectrum and histologic studies.Results. Operations carried out on subcutaneous and orthotopic mouse models under the control of fluorescent imaging using AGAk-IG demonstrate the effectiveness of using a targeted tumour sample to achieve consistent and accurate RMP-resection. Operations under the control of BIC-spectrometry have demonstrated that the proposed substance can effectively help surgeons to locate tumours, determine their edges and constantly check the presence of tumour residues during surgery.Conclusion. The findings demonstrated the high efficiency of AGAk-IG as a potential molecular fluorescent agent for tumour-specific intraoperative imaging in bladder cancer resection, as well as offering great potential for further clinical studies.